Analysis of Success Factors and Business Sustainability by Muslim Women Entrepreneurs Based on Islamic Studies - Zutiasari, Ika; Ita Prihatining Wilujeng; Rizka Dewi Auliya (Open Access Indonesia Journal of Social Sciences, 2024)
Businesses managed by Muslim women entrepreneurs have become an interesting phenomenon in the global economic landscape. This research aims to understand in depth the factors that contribute to the success and sustainability of businesses managed by Muslim women entrepreneurs, using an Islamic perspective as the basis for analysis. This research uses a qualitative approach with a multiple case study design. Data was collected through in-depth interviews with 15 Muslim women entrepreneurs who have businesses that have been running for at least 5 years and are considered successful in their respective industries. Data analysis was carried out using thematic methods, identifying key themes that emerged from the interview data. The research results reveal that the business success factors of Muslim women entrepreneurs include: (1) Integrity and Islamic Business Ethics: Successful Muslim women entrepreneurs demonstrate a strong commitment to the values of honesty, justice and transparency in running their business. (2) Business Knowledge and Competence: The ability to manage finances, marketing and business operations is an important factor in achieving success. (3) Networking and Collaboration: Building strong relationships with customers, suppliers and other business partners contributes to business growth and sustainability. (4) Innovation and Adaptation: The ability to innovate and adapt to market changes is key in facing competition. (5) Devotion and Spirituality: Devotion and the practice of Islamic spirituality provide motivation and strength in facing business challenges. This research provides valuable insight into the factors that contribute to the success and sustainability of businesses managed by Muslim women entrepreneurs. These findings have important implications for Muslim entrepreneurs, policy makers and academics in developing strategies and programs that support business growth and sustainability based on Islamic values.